SPATIAL DISTRIBUTION OF TUBERCULOSIS IN GOMBE STATE USING GEOGRAPHICAL INFORMATION SYSTEMS APPROACH - MAKADI, YILA CAIAPHAS; AHMED, BALKISU Y. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
This research was carried out to examine the spatial distribution of tuberculosis in Gombe State using GIS approach from 2010-2015. Used in this study were secondary data, obtained from the tuberculosis and leprosy control center in Gombe for a period, 2010-2015. Data and information for the research were collected from the eleven local government areas of the State. The Moran I index was used to examine the values of spatial autocorrelation of tuberculosis prevalence in the study area. Additionally, the IDW (Inverse Distance Weighing) method interpolation was employed in this study for identifying the spatial pattern of tuberculosis prevalence. The research revealed there were a number of reported cases of PTB ( Pulmonary Tuberclosis) and EPTB (Extra Pulmonary Tuberclosis) over the years and in the eleven local government areas of the state for the period of study. The pattern showed decreasing and increasing cases between the years with few reported cases of PTB in 2010 in Dukku Local Government Area and escalating prevalence of over 15 percent in 2014. The hotspot regions of high PTB occurrence in 2010 were Dukku, Yamaltu/Deba, Nafada and Kaltungo, while in 2014 the regions of higher occurrence were Shongom, Kwami, Akko, Kaltungo and Nafada. The cold spot regions of low PTB occurrence included Dukku, Balanga, Billiri and Gombe Local government Areas. The study further revealed that the occurrence of tuberculosis among males and females varied and these variations were much higher between males and females in Nafada, Shongom, Kaltungo and Kwami Local Government Areas.